Review of Pleurosignum Vanhöffen, 1914, with re-descriptions, new genera and species in a new Pleurosignum group in Paramunnidae (Isopoda, Asellota), with remarks on Pleurogonium Sars, 1863 - Just, Jean (Zootaxa, 2026)
The paramunnid genus Pleurosignum Vanhöffen, 1914, together with related Antennulosignum Nordenstam, 1933, are reviewed. Following a re-assessment of the 2 genera and 5 known species and description of new species from the Antarctic to temperate southern hemisphere, this group of the Paramunnidae (Pleurosignum/Antennulosignum) is divided into 5 genera and 12 species: Pleurosignum Vanhöffen, 1914: P. elongatum Vanhöffen, 1914 (genotype); P. chilense Menzies, 1962; P. brevispinum sp. nov.; P. sp.; Geliduosignum gen. nov.: G. franklinae sp. nov. (genotype); G. magnum (Vanhöffen, 1914) comb. nov.; G. glacialis sp. nov.; G. menziesi sp. nov.; Tinihekesignum gen. nov.: T. hispidum sp. nov. (genotype); Ateleriosignum gen. nov., A. capensis (Kensley, 1977) comb. nov. (genotype); Antennulosignum Nordenstam, 1933: A. elegans Nordenstam, 1933 (genotype); A. grandis sp. nov. These 5 southern hemisphere genera form a distinctive group in the Paramunnidae, which here is diagnosed as a Pleurosignum group, characterised by the combination of elongate eyestalks, narrow, pointed molar, coxal spines on pereonites 1–7 or 2–7, pleotelson with smooth margin, and bi-ramous uropods of unequally sized rami, protopod hidden or absent.